Comparison of two real-time optimization strategies to maximize the hydrogen production in a dark fermenter. Issue 13 (2018) - Torres, Ixbalank; Vargas, Alejandro; López-Caamal, Fernando; Hernández-Escoto, Héctor
Abstract: Biohydrogen production represents a real alternative to the current energetic problem. It is a clean energetic vector and has a high energy yield. Particularly, hydrogen production by dark fermentation constitutes an attractive alternative to conventional physical/chemical methods. In this article we compare two real-time optimization strategies to online compute the optimal operating conditions of a dark fermentation process for maximizing the hydrogen production, respecting input constraints.